Strong impact of light-induced conical intersections on the spectrum of diatomic molecules - Šindelka, Milan; Moiseyev, Nimrod; Cederbaum, Lorenz S. (Journal of physics. B, Atomic, molecular and optical physics, 2011)
We show that dressing of diatomic molecules by running laser waves gives rise to conical intersections (CIs). Due to the presence of such CIs, the rovibronic molecular motions are strongly coupled. A pronounced impact of the CI on the spectrum of the Na2 molecule is demonstrated via numerical calculation for weak and moderate laser intensity, and an experiment is suggested on this basis. The position of the light-induced CI and the strength of its non-adiabatic couplings can be chosen by changing the frequency and intensity of the used running laser wave. This offers new possibilities of controlling the photo-induced rovibronic molecular dynamics.
Gesehen am 14.10.2022